Within‐Stand Boundary Effects on Snow Water Equivalent Distribution in Forested Areas. Issue 10 (19th October 2020) - Webb, R. W.; Raleigh, M. S.; McGrath, D.; Molotch, N. P.; Elder, K.; Hiemstra, C.; Brucker, L.; Marshall, H. P.
Abstract: Forested areas exhibit high spatial variability in the distribution of snow water equivalent (SWE). Previous work has focused on forested areas with respect to snow accumulation in adjacent clearings. There is generally less snow in forested areas with greater variability relative to open areas due to the influence of tree canopies. However, the length scale of the transition from open areas to forested conditions is uncertain. Hence, the goal of this paper is to determine the length scales associated with forest boundary effects on SWE accumulation distribution patterns within forest stands. To accomplish this, we utilize a unique ground‐penetrating radar data set collected during the NASA SnowEx campaign on Grand Mesa, Colorado, in February 2017 to determine spatial SWE distribution patterns of areas under canopy and in clearings, and the length scales of transitions between these patterns (i.e., the size of within‐stand boundary areas). We define within‐stand boundary areas as the transitional zone from a clearing to relatively stable SWE distribution, or background distribution patterns, within forest stands. The largest within‐stand boundary effect occurred on the leeward side of stands with a mean extent of 44 m, or 4.3 mean canopy heights. In contrast, windward within‐stand boundary effects showed a mean extent of 28 m, or 3.7 mean canopy heights. We present a conceptual framework of the complex wind dynamics that occur in forest stands to explain the within‐stand boundary effects on SWE distribution. Future investigations could improve understanding of this complex process and associated driving variables. Key Points: Boundary effects extend into forested areas 3.7 and 4.3 mean canopy heights on windward and leeward sides of stands, respectively These effects are a result of complex wind dynamics including eddies and spatially varying effective roughness near forest boundaries SWE variability is significantly different in forest boundary affected areas relative to background under canopy variability